2008
DOI: 10.1128/jcm.02216-07
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Vitek 2 in Antimicrobial Susceptibility Testing of Pseudomonas aeruginosa Isolates with Different Mechanisms of β-Lactam Resistance

Abstract: A total of 78 isolates of Pseudomonas aeruginosa grouped according to the phenotype for ceftazidime and imipenem susceptibility/resistance were used to assess the accuracy of the Vitek 2 system in antimicrobial susceptibility testing. Comparisons were made with a MIC gradient test for piperacillin-tazobactam, ceftazidime, aztreonam, imipenem, meropenem, gentamicin, and ciprofloxacin. For the total of 546 isolate-antimicrobial combinations tested, the category agreement was 83.6%, with 2.0, 1.6, and 12.8% very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…Due to this problem, laboratories might consider primary testing of mucoid isolates by disk diffusion. The most notable errors occurred in P. aeruginosa isolates with piperacillin-tazobactam, as has been seen by others (5,7,11,12). Unlike these previous studies that found piperacillin-tazobactam VME rates ranging from 10.2 to 21.7% (5, 7, 10), we found 0 VMEs and only 3 (4.3%) MEs.…”
Section: Discussioncontrasting
confidence: 55%
“…Due to this problem, laboratories might consider primary testing of mucoid isolates by disk diffusion. The most notable errors occurred in P. aeruginosa isolates with piperacillin-tazobactam, as has been seen by others (5,7,11,12). Unlike these previous studies that found piperacillin-tazobactam VME rates ranging from 10.2 to 21.7% (5, 7, 10), we found 0 VMEs and only 3 (4.3%) MEs.…”
Section: Discussioncontrasting
confidence: 55%
“…14,15,17 Concerns regarding the reliability of automated susceptibility testing have been previously described for P. aeruginosa. 22,23 In the current study, disk diffusion was exclusively used for all P. aeruginosa susceptibility testing.…”
Section: Discussionmentioning
confidence: 99%
“…Minor errors were found in 5.1% of strains, and major and very major errors were found in 1.6% and 0.3% of strains, respectively in the same study. 21 Annarita Mazzariol et al 22 demonstrated that VITEK 2 could be used with confidence for identifying resistance to several antimicrobial agents against P. aeruginosa including imipenem.…”
Section: Discussionmentioning
confidence: 99%